Learning with Others : Collaboration as a Pathway to College Student Success - Conrad, Clifton; Lundberg, Todd (Book collections on Project MUSE., 2022)
Outlining strategies for identifying and dismantling barriers to participation, Learning with Others will pique interest among faculty, students, and administrators in higher education and a wide range of external stakeholders--from families and communities to policymakers and funders.Clifton Conrad and Todd Lundberg.